Copper Bonding Wire

By controlling the chemical bonding states of Cu(I) and Cu(II) in copper bonding wires, the issues of low bonding properties and productivity are addressed, enabling stable mass production and practical use in semiconductor devices.

JP7610570B2Active Publication Date: 2025-01-08NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022501085
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-21
Filing Date
2021-02-19
Publication Date
2025-01-08
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Copper bonding wires exhibit low bonding properties and require special conditions like scrubbing, which increases bonding time and reduces productivity, hindering their widespread use in semiconductor devices.

Method used

A copper bonding wire with controlled chemical bonding states of Cu(I) and Cu(II) ratios, as measured by X-ray Photoelectron Spectroscopy (XPS), within specific ranges, along with optional dopants like Pd, Pt, and Rh, to enhance bonding properties and stability.

Benefits of technology

The copper bonding wire achieves good bonding properties with reduced scrubbing, improves loop shape stability, and extends capillary life, facilitating stable mass production and practical use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610570000001
    Figure 0007610570000001
Patent Text Reader

Abstract

Provided is a copper bonding wire which can exhibit satisfactory bondability even when scrubbing during bonding is reduced. The copper bonding wire is characterized in that, when the sum total of the content ratios of Cu, Cu2O, CuO and Cu(OH)2 on the surface of the wire as measured by X-ray photoelectron spectroscopy (XPS) is 100%, Cu[II] / Cu[I] which is the ratio of the total content ratio (Cu[II]) of CuO and Cu(OH)2 which correspond to bivalent Cu to the content ratio (Cu[I]) of Cu2O which corresponds to monovalent Cu is 0.8 to 12.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to copper bonding wire. [Background technology]

[0002] In semiconductor devices, electrodes formed on a semiconductor chip are connected to electrodes on a lead frame or substrate by bonding wires. Until now, gold (Au) has been the mainstream material for bonding wires, but research and development into replacing it with copper (Cu) has been progressing, mainly for LSI applications (e.g., Patent Documents 1 to 3). In addition, in power semiconductor applications, it is expected that Cu will be used as a replacement because of its high thermal conductivity and fusing current, which makes it highly efficient and reliable. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 61-48543 [Patent Document 2] Special Publication No. 2018-503743 [Patent Document 3] International Publication No. 2017 / 221770 Summary of the Invention [Problem to be solved by the invention]

[0004] One problem with mass production of mounting processes using copper bonding wire (hereinafter simply referred to as "copper wire") is that special bonding conditions are required due to low bondability, which is a cause of delays in the widespread use of this technology.

[0005] Wedge bonding, which bonds copper wire to an electrode on a substrate, tends to result in low bonding strength. Therefore, as a method to improve the bondability of copper wire, a scrubbing function is often used, which moves the capillary or sample stage horizontally several times at low frequency during bonding. In general bonding of bonding wire, ultrasonic vibration (60 to 120 kHz) is used, but since bonding with conventional copper wire is insufficient with ultrasonic vibration alone, a scrubbing function is used in addition to ultrasonic vibration. The scrubbing movement direction is generally parallel to the wire direction, but in some cases, an arc shape (a combination of a parallel direction and a direction perpendicular to the parallel direction) is used in the wire direction.

[0006] This scrubbing function causes problems such as longer bonding time, lowering productivity, and inducing disturbance of the loop shape. Scrubbing is a special bonding condition that was not used with conventional gold wire, and if it were possible to reduce the number of scrubs and the amount of scrubbing movement with copper wire as well, it would be possible to improve productivity and contribute to expanding the practical use of copper wire.

[0007] An object of the present invention is to provide a copper bonding wire that exhibits good bondability even when scrubbing during bonding is reduced. [Means for solving the problem]

[0008] As a result of intensive research into the above problems, the inventors have found that the above problems can be solved by a copper bonding wire having the following configuration, and have completed the present invention. That is, the present invention includes the following. [1] A copper bonding wire characterized in that Cu[II] / Cu[I], which is the ratio of the total percentage (Cu[II]) of CuO and Cu(OH)2 corresponding to divalent Cu to the percentage (Cu[I]) of Cu2O corresponding to monovalent Cu, where the sum of the percentages of Cu, Cu2O, CuO, and Cu(OH)2 on the wire surface measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, is in the range of 0.8 to 12. [2] The copper bonding wire according to [1], characterized in that the ratio of the proportion of Cu(OH)2 [Cu(OH)2] to the proportion of CuO [CuO], [Cu(OH)2] / [CuO], is in the range of 1 to 5.5, as measured by the X-ray photoelectron spectroscopy (XPS). [3] The copper bonding wire according to [1] or [2], characterized in that the ratio of CuO to CuO, [CuO] / [Cu2O], measured by the X-ray photoelectron spectroscopy (XPS), is in the range of 0.3 to 6. [4] The copper bonding wire according to any one of [1] to [3], wherein the sum of the Cu[I] and the Cu[II] is 50% or more. [5] A copper bonding wire according to any one of [1] to [4], characterized in that it contains one or more elements selected from the group consisting of Pd, Pt, Ag and Rh, and the total concentration of these elements is in the range of 100 to 6000 ppm by mass. [6] The copper bonding wire according to any one of [1] to [5], having a diameter of 15 μm or more and 100 μm or less. [7] The copper bonding wire according to any one of [1] to [6], which is for use in a semiconductor device. Effect of the Invention

[0009] According to the present invention, it is possible to provide a copper bonding wire that exhibits good bondability even when scrubbing during bonding is reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below based on preferred embodiments thereof.

[0011] [Copper bonding wire] The copper bonding wire of the present invention is characterized in that Cu[II] / Cu[I], which is the ratio of the total proportion (Cu[II]) of CuO and Cu(OH)2 corresponding to a valence of Cu to the proportion (Cu[I]) of Cu2O corresponding to a valence of Cu, is in the range of 0.8 to 12, where the sum of the proportions of Cu, Cu2O, CuO, and Cu(OH)2 on the wire surface measured by X-ray photoelectron spectroscopy (XPS) is 100%.

[0012] By measuring the surface of a copper wire by X-ray photoelectron spectroscopy (XPS), the chemical bond state of copper (Cu) elements present near the surface of the copper wire (usually the analysis depth is about several nm) can be analyzed. The present inventors have found that the chemical bond state (charge state) of the Cu element on the copper wire surface correlates with the properties of the copper wire, and have realized a copper wire that exhibits desired properties by controlling the chemical bond state of the Cu element.

[0013] The inventors have found that the ratio of Cu substances in the chemical bond state of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) is important in relation to the properties of copper wire, including bondability at low scrub. Note that the Cu substance in the chemical bond state of Cu corresponds to the Cu element in the metallic state (Cu0 valence).

[0014] In the present invention, the term "proportions of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS)" refers to the proportions of Cu substances in the chemically bonded states of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS).

[0015] When the total percentage of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, the ratio of the total percentage (Cu[II]) of CuO and Cu(OH)2 corresponding to divalent Cu to the percentage (Cu[I]) of Cu2O corresponding to monovalent Cu, is Cu[II] / Cu[I], which is in the range of 0.8 to 12. This makes it possible to realize a copper wire that exhibits good bondability even when scrubbing during bonding is reduced.

[0016] Here, the proportion of Cu2O equivalent to Cu monovalent (Cu[I]) refers to the proportion of Cu material in a Cu2O chemical bond state when the total of Cu materials in the Cu, Cu2O, CuO, and Cu(OH)2 chemical bond states measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, as described above.

[0017] Similarly, the total percentage of CuO and Cu(OH)2 equivalent to a valence of Cu (Cu[II]) refers to the total percentage of Cu substances in chemically bonded states of CuO and Cu(OH)2 when the total of Cu substances in chemically bonded states of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, as mentioned above.

[0018] By measuring the surface of a copper bonding wire by XPS, it is possible to accurately identify the Cu monovalent and Cu divalent present on the surface of the copper wire and calculate the concentration. By controlling the ratio of Cu monovalent and Cu divalent determined by the XPS measurement, it is possible to realize a copper wire that exhibits good bondability even if scrubbing during bonding is reduced. In addition, AES (Auger spectroscopy), SEM (secondary electron microscope), TEM (transmission electron microscope), etc. have been used as conventional analytical methods for analyzing the surface of a thin copper wire with a diameter of about 10 to 100 μm. However, it is difficult to accurately analyze a Cu substance in a specific chemical bond state by measuring the chemical bond state of the Cu element on the copper wire surface using these methods. The present inventors performed AES and TEM analyses on the surfaces of several copper wires, but confirmed that the characteristics of the copper wire surface identified by these methods do not necessarily correlate with the bonding characteristics of the copper wire, particularly the bondability at low scrubbing, which is the subject of the present invention. On the other hand, it has been discovered that by using copper wire in which the ratio of Cu1 and Cu2 valences determined by XPS measurement is controlled, good bondability can be stably achieved even when scrubbing during bonding is reduced, and stable mass production can be realized.

[0019] Hereinafter, this condition regarding the ratio Cu[II] / Cu[I] will also be referred to as “Condition 1.”

[0020] From the viewpoint of realizing a copper wire having even better bondability at low scrubbing, it is preferable to increase the ratio of divalent Cu present near the surface of the copper wire relative to the ratio of monovalent Cu, and the lower limit of the ratio Cu[II] / Cu[I] is preferably 0.9 or more, more preferably 1 or more, and even more preferably 1.2 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.8 or more, 2 or more, 2.2 or more, 2.4 or more, 2.5 or more, 2.6 or more, 2.8 or more, or 3 or more. It is presumed that such an effect is influenced by the fact that the protective function of the copper wire surface is enhanced by (a Cu substance equivalent to) divalent Cu, and that the progress of oxidation can be suppressed by controlling the monovalent Cu.

[0021] In order to realize a copper wire having even better bondability at low scrub, the upper limit of the ratio Cu[II] / Cu[I] is preferably 11.5 or less, more preferably 10 or less, and even more preferably 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, or 7 or less.

[0022] In a copper wire having a surface with a Cu[II] / Cu[I] ratio in the above range as measured by X-ray photoelectron spectroscopy (XPS), the gap and unevenness at the bonding interface can be reduced by normal ultrasonic vibration to increase adhesion, and the diffusion of Cu to the bonding partner through the bonding interface is further promoted, so that it is considered that good bonding can be achieved even if the number of scrubs and the amount of movement are reduced. In this regard, the present inventors have confirmed that simply separating and individually adjusting the ratios of Cu[I] and Cu[II] near the surface of the copper wire causes variations in bonding and makes it difficult to achieve the desired characteristics, and that it is important to control the ratio Cu[II] / Cu[I].

[0023] From the viewpoint of obtaining the effect of controlling the ratio Cu[II] / Cu[I], the lower limit of the sum of Cu[I] and Cu[II] is preferably 50% or more, more preferably 60% or more. From the viewpoint of ease of manufacturing the wire, the upper limit of this ratio is preferably 95% or less or 90% or less.

[0024] The bondability of copper wire is affected little by the planar distribution of Cu[I] and Cu[II] on the surface of the copper wire, the distribution form of Cu substances in each state of Cu[I] and Cu[II] (granular distribution, linear distribution, planar distribution, etc.), and the surface form of the copper wire, but is greatly affected by the ratio Cu[II] / Cu[I]. In this regard, the analysis depth of XPS analysis is about a few nm, and no correlation was found between the distribution of Cu[I] and Cu[II] at that analysis depth and bondability.

[0025] The inventors have also discovered that by controlling the chemical bonding state of the Cu material present near the surface of the copper wire, it is possible to realize a copper wire that exhibits good bondability even when scrubbing during bonding is reduced, and also has excellent loop shape stability.

[0026] When copper wire is deformed to form a loop, the wire can bend or bend, which can cause defects such as contact between adjacent wires. For example, because gold wire is easy to deform (shape), trapezoidal or M-shaped loop shapes have been used to form long wire loops (long spans). However, forming a trapezoidal or M-shaped loop with copper wire can cause the wire to bend or break. Also, when forming a short wire loop (short span), if there is a large difference in height between the semiconductor element and the substrate, copper wire tends to frequently cause loop collapse and poor bonding. As such, there have been concerns that the unstable loop shape of copper wire makes it difficult to manage manufacturing during mounting and reduces yields.

[0027] In contrast, a preferred embodiment of the present invention is characterized in that the ratio of Cu(OH)2, [Cu(OH)2], to the ratio of CuO, [CuO], [Cu(OH)2] / [CuO], is in the range of 1 to 5.5, as measured by X-ray photoelectron spectroscopy (XPS).

[0028] Here, the percentage of CuO measured by X-ray photoelectron spectroscopy (XPS) [CuO] refers to the percentage of Cu substances in the chemical bond state of CuO when the total of Cu substances in the chemical bond states of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, as described above.

[0029] Similarly, the percentage of Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) [Cu(OH)2] refers to the percentage of Cu material in the chemical bond state of Cu(OH)2 when the total of Cu materials in the chemical bond states of Cu, Cu2O, CuO, and Cu(OH)2 measured by XPS is taken as 100%.

[0030] Hereinafter, this condition regarding the ratio [Cu(OH)2] / [CuO] will also be referred to as “Condition 2.”

[0031] By having the ratio [Cu(OH)2] / [CuO] in the range of 1 to 5.5, it is possible to suppress defects such as collapse, bending, and sagging during loop formation, and a copper wire with excellent loop shape stability can be realized even when forming a long-span loop or a short-span, high-step loop.

[0032] From the viewpoint of realizing a copper wire having even more excellent loop shape stability, the lower limit of the ratio [Cu(OH)2] / [CuO] is more preferably 1.1 or more, further preferably 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, or more than 1.5.

[0033] It was confirmed that the sliding property between the wire surface and the capillary affects the stability of the loop shape in the case of copper wire. When the wire is formed into a loop, tension and deformation are applied to the wire, causing the wire to rub against the inner wall and tip of the capillary. Aluminum (Al) oxides are generally used as the material for the capillary, and ordinary alumina (Al2O3) and alumina containing zirconium (Zr) are often used. The inventors found that the sliding property with this Al-based oxide is affected by Cu substances in a chemical bond state equivalent to Cu divalent present near the surface of the copper wire, and that the ratio of Cu(OH)2 to CuO has a large influence on this. It is believed that an increase in the ratio of Cu(OH)2 reduces friction with the Al-based oxide, and that a reduction in the ratio of CuO reduces scraping and snagging.

[0034] In order to realize a copper wire having even more excellent loop shape stability, the upper limit of the ratio [Cu(OH)2] / [CuO] is more preferably 5.4 or less, further preferably 5.3 or less, 5.2 or less, 5.1 or less, or 5 or less.

[0035] By forming a surface having a ratio [Cu(OH)2] / [CuO] within the above-mentioned preferred range, a copper wire with excellent loop shape stability can be realized even when a long-span loop or a short-span high-step loop is formed. For example, when a long-span trapezoidal loop is formed, the loop shape consisting of a horizontal part and an inclined part of the wire can be stabilized even if the wire length is 4 mm or more. Also, for example, when a short-span high-step loop is formed, even if the wire length is 0.5 mm or less and the difference in height between two joints (i.e., a first joint with an electrode on a semiconductor chip and a second joint with an electrode on a lead frame or a circuit board) is 0.1 mm or more, the loop shape can be stabilized by suppressing collapse and sagging.

[0036] The inventors further discovered that by controlling the chemical bonding state of the Cu substance present near the surface of the copper wire, it is possible to realize a copper wire that exhibits good bondability even when scrubbing during bonding is reduced, and that provides a good capillary life.

[0037] There are concerns that copper wires are prone to damage such as clogging of the capillary and the generation of deposits early on. When connecting a large number of wires in the bonding process, the capillary hole can become clogged and the inner wall and tip can become dirty, causing poor bonding, and the capillary must be replaced more frequently to avoid such defects. Problems with capillary replacement include the interruption of production due to equipment shutdowns and the need to take measures such as increasing the number of workers. Furthermore, in the future, there will be a demand for thinner copper wires to meet the needs for high-density packaging, but there is a concern that the use of thinner copper wires will shorten the service life of the capillary because the gap between the capillary and the wire becomes smaller (the wire-passing hole becomes narrower).

[0038] In contrast, a preferred embodiment of the present invention is characterized in that the ratio of CuO to CuO, [CuO] / [CuO], measured by X-ray photoelectron spectroscopy (XPS), is in the range of 0.3 to 6.

[0039] Here, the percentage of Cu2O measured by X-ray photoelectron spectroscopy (XPS) [Cu2O] refers to the percentage of Cu substances in the chemically bonded state of Cu2O when the total of Cu substances in the chemically bonded states of Cu, Cu2O, CuO, and Cu(OH)2 measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, as described above.

[0040] The proportion of CuO [CuO] measured by X-ray photoelectron spectroscopy (XPS) is as described above in relation to condition 2.

[0041] Hereinafter, this condition regarding the ratio [CuO] / [Cu2O] will also be referred to as “Condition 3.”

[0042] By setting the ratio [CuO] / [Cu2O] in the range of 0.3 to 6, the service life of the capillary before replacement in the mass production process of bonding (also simply referred to as "capillary life") can be improved.

[0043] From the viewpoint of further improving the capillary life, the lower limit of the ratio [CuO] / [Cu2O] is more preferably 0.4 or more, further preferably 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, or 1 or more.

[0044] It is believed that the two oxides, CuO and Cu2O, affect the capillary lifespan by interacting with each other to cause scrapes and scratches on the capillary and wire surfaces, and clogging of the capillary wire passage holes, etc. CuO forms a dense film, which contributes to reducing wear caused by friction with the Al-based oxides that make up the capillary, while Cu2O is formed relatively quickly and contains lattice defects and voids, which makes it susceptible to scraping.

[0045] In this regard, the inventors have found that it is difficult to improve clogging and wear of the wire passage hole by simply separating and individually adjusting the proportions of CuO and Cu2O near the surface of the copper wire, but that by controlling both of them together and controlling the ratio [CuO] / [Cu2O], the capillary life can be significantly improved.

[0046] From the viewpoint of realizing excellent capillary life while realizing good low-temperature bondability, the upper limit of the ratio [CuO] / [CuO] is more preferably 5.5 or less, further preferably 5 or less, 4.5 or less, 4 or less, 3.8 or less, 3.6 or less, 3.5 or less, 3.4 or less, 3.2 or less, 3 or less, or 2.8 or less.

[0047] In the copper wire of the present invention, when the total of Cu substances in a chemically bonded state of Cu, Cu2O, CuO, and Cu(OH)2 on the wire surface measured by X-ray photoelectron spectroscopy (XPS) is taken as 100%, the proportion of Cu substances in a chemically bonded state of Cu is preferably 5% or more, more preferably 10% or more. The upper limit of the proportion is preferably 50% or less, more preferably 40% or less.

[0048] The copper wire of the present invention is made of copper or a copper alloy. The copper content in the wire is not particularly limited as long as it does not impair the effects of the present invention. For example, the copper content in the wire may be 95% by mass or more, and is preferably 96% by mass or more, 97% by mass or more, 98% by mass or more, 99% by mass or more, 99.2% by mass or more, 99.4% by mass or more, or 99.5% by mass or more.

[0049] The copper wire of the present invention may further contain a dopant. Any dopant capable of improving the properties of the copper wire may be contained, but it is preferable to contain one or more selected from the group consisting of Pd, Pt, Ag and Rh. By containing such a specific dopant and satisfying the above-mentioned condition 1, the storage life in the atmosphere can be improved.

[0050] The copper wire of the present invention preferably contains at least one selected from the group consisting of Pd, Pt, Ag, and Rh in a total amount of 100 to 6000 ppm by mass when the entire wire is taken as 100 mass %. Therefore, in a preferred embodiment, the copper bonding wire of the present invention contains at least one selected from the group consisting of Pd, Pt, Ag, and Rh, and is characterized in that the total concentration of these elements is in the range of 100 to 6000 ppm by mass.

[0051] The lower limit of the total content of the dopants in the copper wire is more preferably 150 mass ppm or more, further preferably 200 mass ppm or more, 250 mass ppm or more, or 300 mass ppm or more. In addition, the upper limit of the total content is more preferably 5500 mass ppm or less, further preferably 5000 mass ppm or less, 4500 mass ppm or less, 4000 mass ppm or less, 3500 mass ppm or less, or 3000 mass ppm or less, from the viewpoint of improving the storage life in the atmosphere while suppressing an increase in wire hardness.

[0052] After the copper wire is wound around a spool to form a wound body, the wound body is sealed in a barrier bag that blocks oxygen, moisture, and the like and shipped. Then, the barrier bag is opened before the wire is used for connection between electrodes in the manufacture of a semiconductor device. The expiration date of the wire after opening is usually about 2 to 6 days. By containing one or more selected from the group consisting of Pd, Pt, Ag, and Rh in the above-mentioned suitable content while satisfying condition 1, the storage life in the atmosphere after opening the barrier bag can be improved. For example, even if the wire is stored in the atmosphere for 7 days after opening the barrier bag, a copper wire can be obtained that has good bondability under low scrub conditions and good loop shape stability. This effect is believed to be due to the fact that by containing one or more selected from the group consisting of Pd, Pt, Ag and Rh in the above-mentioned preferred contents while satisfying the ratio Cu[II] / Cu[I] of condition 1, the precious metal elements Pd, Pt, Ag and Rh suppress the growth of Cu2O, which is monovalent Cu, and maintain the effect of promoting the formation of divalent Cu for a long period of time even while the wire is stored in air, thereby enhancing the effect of maintaining the ratio Cu[II] / Cu[I] within the appropriate range of the present invention.

[0053] In the copper bonding wire of the present invention, the remainder other than the dopant may consist of copper and unavoidable impurities.

[0054] The diameter of the copper bonding wire of the present invention is not particularly limited and may be appropriately determined depending on the specific purpose, but may be preferably 15 μm or more, 18 μm or more, or 20 μm or more, etc. The upper limit of the diameter is not particularly limited and may be, for example, 200 μm or less, 150 μm or less, or 100 μm or less, etc. In one embodiment, the diameter of the copper bonding wire of the present invention is 15 μm or more and 100 μm or less.

[0055] The copper bonding wire of the present invention can be used to connect the electrodes on a semiconductor chip and the electrodes on a lead frame or a circuit board in the manufacture of semiconductor devices. The first connection (1st bonding) with the electrodes on the semiconductor chip may be either a ball bonding or a wedge bonding. In ball bonding, the tip of the wire is heated and melted by arc heat input, and after forming a ball (FAB: Free Air Ball) by surface tension, this ball part is pressure-bonded onto the electrode of the heated semiconductor element. In wedge bonding, without forming a ball, the wire part is pressure-bonded onto the electrode by applying heat, ultrasonic waves, and pressure. The second connection (2nd bonding) with the electrodes on the lead frame or the circuit board can be a wedge bonding. According to the copper bonding wire of the present invention that satisfies the above-mentioned condition 1, good bondability can be exhibited even when the scrub during bonding is reduced. Furthermore, by satisfying the above-mentioned condition 2, excellent loop shape stability can be achieved even when forming a long-span loop or a short-span high-step loop. By satisfying the above-mentioned condition 3, the capillary life can be improved. Thus, the present invention significantly contributes to the practical expansion of copper wires.

[0056] <Measurement and Evaluation Method of Copper Bonding Wire by XPS> Hereinafter, the measurement and evaluation method of copper bonding wire by X-ray photoelectron spectroscopy (XPS) will be described.

[0057] - Preparation of Measurement Sample - The measurement sample can be prepared by winding the copper wire around the sample stage. Specifically, a glass plate is prepared as the sample stage, and the copper wire is wound around the glass plate multiple times to prepare the measurement sample. At this time, the copper wire is wound around the glass plate such that (i) the copper wire is densely wound multiple times and the glass plate serving as the sample stage cannot be seen, and (ii) the surface of the obtained measurement sample becomes flat. Here, the "flat" regarding the surface of the measurement sample means that the surface of the measurement sample obtained by winding the copper wire around the sample stage multiple times has no extreme unevenness and is flat to the extent of being a plane substantially parallel to the main surface of the sample stage.

[0058] Here, when the copper wire is subjected to the measurement, no special pretreatment is required, and the copper wire may be measured in the same state as when it is used for connection between electrodes in the manufacture of a semiconductor device. As described above, after the copper wire is manufactured, it is sealed in a barrier bag that blocks oxygen, moisture, and the like and shipped. Then, the barrier bag is opened before the copper wire is used for connection between electrodes in the manufacture of a semiconductor device. The barrier bag is opened in a clean room where the semiconductor device is manufactured, and the storage period after opening is usually about 2 to 6 days. Therefore, after the barrier bag is opened, the copper wire may be subjected to the measurement before 3 days have passed in the clean room or an environment equivalent thereto. Preferably, the measurement sample is prepared immediately after opening the barrier bag (for example, within 3 hours, within 2 hours, within 1 hour, or within 30 minutes), and the measurement sample is placed in the vacuum atmosphere of the XPS measurement device and XPS measurement is performed immediately.

[0059] -Measurement and evaluation using XPS- The obtained measurement sample is measured by XPS to obtain the Cu2p3 / 2, CuLMM, and Ols spectra. Here, Cu2p3 / 2 is a spectrum derived from electrons (photoelectrons) in the Cu 2p3 / 2 orbital, CuLMM is a spectrum derived from Auger electrons related to the LMM transition of Cu, and O1s is a spectrum derived from electrons in the oxygen (O) 1s orbital.

[0060] The XPS measurement can be performed under the conditions described in the section [Measurement and evaluation of copper bonding wire by XPS] below. It is preferable that the measurement area (detection target area) of the XPS is an area with a diameter of at least 100 μm, and the number of measurements is two or more. The above conditions 1 to 3, as well as the ratio of Cu substances in each of the above-mentioned chemical bond states, are based on the results of measurement of a measurement area of ​​at least such value.

[0061] Next, the detected spectrum is analyzed. The spectrum is analyzed by waveform analysis using the analysis software attached to the XPS device, and separated according to the chemical bond state of Cu. The ratio of each chemical bond state of Cu can be calculated according to the following steps (1) to (3). (1) Using the Cu2p3 / 2 spectrum, separate the waveform of the sum of Cu[0] + Cu[I] and the waveform of Cu[II] and determine the proportion of each. (2) Using the CuLMM spectrum, separate the Cu[0] waveform and the Cu[I] waveform and determine their respective proportions. (3) Using the Ols spectrum, separate the CuO and Cu(OH)2 waveforms and determine their respective proportions. Adjust the proportion of the O2 component (derived from Cu2O) in the Ols spectrum to be half the proportion of Cu[I].

[0062] <Manufacturing method of copper bonding wire> An example of a method for producing a copper bonding wire according to the present invention will be described.

[0063] Raw copper having a purity of 3N to 6N (99.9 to 99.9999 mass%) is processed into a large diameter by continuous casting, and then thinned to the final wire diameter by wire drawing.

[0064] When dopants are added, a copper alloy containing the dopant at the required concentration may be used as the raw material. When dopants are added, high-purity dopant components may be added directly, or a mother alloy containing about 1% of the dopant component may be used. Alternatively, the dopant component may be incorporated by depositing it on the wire surface during the wire manufacturing process. In this case, it may be incorporated at any point in the wire manufacturing process, or it may be incorporated in multiple processes. The deposition method may be selected from (1) application of an aqueous solution → drying → heat treatment, (2) plating method (wet method), or (3) vapor deposition method (dry method).

[0065] The wire drawing can be performed using a continuous wire drawing machine that can accommodate a plurality of diamond-coated dies. If necessary, heat treatment may be performed during the wire drawing process. After the wire drawing process, heat treatment is performed.

[0066] -Control of the ratio Cu[II] / Cu[I]- Below, we will explain suitable heat treatment conditions and surface properties before heat treatment from the perspective of achieving a copper bonding wire in which the ratio Cu[II] / Cu[I] measured by X-ray photoelectron spectroscopy (XPS) is within a specified range.

[0067] In the heat treatment process of the copper wire, it is preferable to simultaneously increase the heating rate and the cooling rate of the wire by using a method of continuously heating the copper wire while sweeping it in a heating furnace. That is, from the viewpoint of controlling the Cu valence ratio Cu[II] / Cu[I] on the copper wire surface within a predetermined range, it is preferable to rapidly heat and rapidly cool the copper wire in the heat treatment process.

[0068] In detail, when the maximum temperature in the heating furnace is T (°C) and the travel time from the inlet of the heating furnace to the maximum temperature region in the furnace is H (seconds), the tentative (apparent) heating rate is expressed as T / H (°C / second). Regarding the cooling rate, when the travel time from the maximum temperature region in the furnace to the outlet of the heating furnace is C (seconds), the tentative (apparent) cooling rate is expressed as T / C (°C / second). The tentative heating rate T / H is preferably 400°C / second or more, more preferably 500°C / second or more or 600°C / second or more. The upper limit of the T / H is not particularly limited, and may be, for example, 2000°C / second or less or 1500°C / second or less. The tentative cooling rate T / C is preferably 500°C / second or more, more preferably 600°C / second or more or 700°C / second or more. The upper limit of the T / C is not particularly limited, and may be, for example, 3000°C / sec or less, 2500°C / sec or less, or 2000°C / sec or less. As a method for realizing such a tentative heating rate and tentative cooling rate, for example, it is preferable to optimize the flow rate of the atmosphere gas, the position of the atmospheric gas inlet, or the length, diameter, and shape of the atmospheric gas flow pipe in the furnace, and to optimize the shape, length, position, and set temperature of the heater part. For example, in order to increase the tentative heating rate, a heater part may be installed near the entrance of the heating furnace to increase its set temperature, and in order to increase the tentative cooling rate, a method such as increasing the flow rate of the atmosphere gas on the cooling side may be adopted. In addition to setting the heating rate and cooling rate in the heat treatment process to the above-mentioned preferred range, the stability of oxides, hydroxides, etc. on the copper wire surface may be changed by controlling the maximum temperature T in the heating furnace in the range of 400 to 900°C, and the ratio Cu[II] / Cu[I] may be advantageously adjusted to the range of 0.8 to 12. Preferably, the tentative heating rate T / H is set to 600°C / sec or more, and the tentative cooling rate T / C is set to 700°C / sec or more, which contributes to adjusting the ratio Cu[II] / Cu[I] to a suitable range of 2 to 10.

[0069] In addition, from the viewpoint of controlling the ratio Cu[II] / Cu[I] within a predetermined range, it is also preferable to reduce the organic matter that adheres to and remains on the surface of the copper wire in the wire drawing process. In the copper wire drawing process, a water- and oil-based lubricant is usually used to reduce friction between the copper wire and the die surface. By using an oil-based lubricant that is easy to volatilize during heat treatment, such as a low-molecular-weight lubricant with a low melting point, it is also possible to promote the generation of Cu2 and adjust the ratio of Cu1. It is presumed that this is due to the fact that the protective function of the copper wire surface is enhanced by Cu2 (Cu substance equivalent to Cu2) and that the progress of oxidation can be suppressed by controlling the Cu1 value.

[0070] -Control of the ratio [Cu(OH)2] / [CuO]- In order to control the ratio [Cu(OH)2] / [CuO], in addition to the heat treatment conditions of rapid heating and rapid cooling described above, it is preferable to water-cool the wire near the outlet of the heating furnace.

[0071] It is believed that the formation of CuO can be suppressed by cooling the wire in water at a high temperature, and the formation of Cu(OH)2 can be promoted by passing the wire through water at a high temperature, thereby advantageously adjusting the ratio [Cu(OH)2] / [CuO] to a predetermined range. The ratio [Cu(OH)2] / [CuO] can be adjusted to the above-mentioned preferred range by optimizing the cooling time, water temperature, and the distance from the furnace outlet to the cooling water during water cooling. The water used for water cooling may contain a small amount of a surfactant. The surfactant can also improve the loosening property of the copper wire when it is used.

[0072] -Control of the ratio [CuO] / [Cu2O]- In controlling the ratio [CuO] / [Cu2O], in addition to the above-mentioned heat treatment conditions of rapid heating and rapid cooling, it is preferable to optimize the oxygen partial pressure and the amount of water vapor in the gas atmosphere used in the heat treatment process.

[0073] The higher the oxygen partial pressure and the amount of water vapor, the more the formation of CuO is promoted, and the ratio [CuO] / [Cu2O] tends to increase.

[0074] [Semiconductor Devices] A semiconductor device can be manufactured by connecting electrodes on a semiconductor chip to electrodes on a lead frame or a circuit board using the copper bonding wire for a semiconductor device of the present invention.

[0075] In one embodiment, the semiconductor device of the present invention includes a circuit board, a semiconductor chip, and a copper bonding wire for electrically connecting the circuit board and the semiconductor chip, and is characterized in that the copper bonding wire is the copper bonding wire of the present invention.

[0076] In the semiconductor device of the present invention, the circuit board and the semiconductor chip are not particularly limited, and a known circuit board and a semiconductor chip that can be used to configure a semiconductor device may be used. Alternatively, a lead frame may be used instead of the circuit board. For example, a semiconductor device including a lead frame and a semiconductor chip mounted on the lead frame may be used, as in the semiconductor device described in JP-A-2002-246542.

[0077] Examples of the semiconductor device include various semiconductor devices used in electrical products (e.g., computers, mobile phones, digital cameras, televisions, air conditioners, solar power generation systems, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0078] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the examples shown below.

[0079] (sample) First, the method of producing the sample will be described. The raw material of the wire, Cu, had a purity of 99.9% by mass or more (3N) to 99.999% by mass or more (5N) with the remainder consisting of inevitable impurities. Such copper of the specified purity was produced by continuous casting to have a wire diameter of several mm. When dopants Pd, Pt, and Ag were added, Pd, Pt, and Ag had a purity of 99% by mass or more with the remainder consisting of inevitable impurities, or a mother alloy in which the dopant was mixed with Cu at a high concentration was used. Then, the dopant was added to the copper of the specified purity so that the dopant content became a target value, and the wire was produced by continuous casting to have a wire diameter of several mm. The obtained wire was subjected to drawing to produce a wire with a wire diameter of 0.3 to 1.4 mm. A commercially available lubricant was used for drawing, and the drawing speed was set to 30 to 200 m / min. The wire was drawn using multiple dies with area reductions ranging from 10 to 26% (more than half of the dies had area reductions of 10 to 21%) until the final wire diameter was reached. If necessary, heat treatments at 200 to 600°C for 5 to 15 seconds were performed 0 to 2 times during the wire drawing process. The final wire diameter was set to 20 μm.

[0080] After processing, the wire was continuously heated while being swept through a heat treatment furnace. The maximum temperature in the furnace was 400-850°C, and heat treatment was performed while 5vol% H2-N2 gas was flowing through the furnace. When the maximum temperature in the furnace is T (°C), the travel time from the furnace entrance to the maximum temperature range in the furnace is H (seconds), and the travel time from the maximum temperature range in the furnace to the furnace exit is C (seconds), the tentative (apparent) heating rate is expressed as T / H (°C / second), and the tentative cooling rate is expressed as T / C (°C / second). In the embodiment, the tentative heating rate T / H is in the range of 400-1500°C / second, and the tentative cooling rate T / C is in the range of 500-2000°C / second. In the comparative example, T / H is less than 400°C / second, and T / C is less than 500°C / second, which is an example of a normal manufacturing condition for copper bonding wire.

[0081] (Testing and Evaluation Methods) The test and evaluation methods are explained below.

[0082] [Measurement and evaluation of copper bonding wire using XPS] 1. Preparation of Measurement Samples The copper bonding wires produced in the examples and comparative examples were sealed in a nitrogen atmosphere using a commercially available barrier bag, and then opened within one week. Within two days after opening, the following measurement samples were prepared and placed in the vacuum chamber of the XPS device. The measurement samples were prepared by wrapping the wire around a 10 mm wide glass plate. When preparing the measurement samples, the copper bonding wire was wrapped around the glass plate so that (i) the wire was densely packed in multiple layers so that the glass was not visible, and (ii) the surface of the measurement sample obtained was flat.

[0083] 2. Measurement and evaluation by XPS The measurement sample obtained in 1 above was subjected to XPS measurement under the following conditions, and the spectra of Cu2p3 / 2, CuLMM, and Ols were detected. Measurement equipment: PHI Quantera II ·Achieved vacuum level: approx. 1×10 -8 Torr X-ray source: Monochromated Al (1486.6 eV) X-ray beam diameter: 100μmΦ(25W, 15kV) Detection area: ≧10000μm 2 ·Photoelectron extraction angle: 45 degrees

[0084] The detected spectrum was analyzed by waveform analysis using the analysis software attached to the XPS device, and separated according to the chemical bond state of Cu. The proportion of each chemical bond state of Cu was calculated according to the following steps (1) to (3). (1) Using the Cu2p3 / 2 spectrum, separate the waveform of the sum of Cu[0] + Cu[I] and the waveform of Cu[II] and determine the proportion of each. (2) Using the CuLMM spectrum, separate the Cu[0] waveform and the Cu[I] waveform and determine their respective proportions. (3) Using the Ols spectrum, separate the CuO and Cu(OH)2 waveforms and determine their respective proportions. Adjust the proportion of the O2 component (derived from Cu2O) in the Ols spectrum to be half the proportion of Cu[I].

[0085] [Performance test and evaluation of copper bonding wire] Bonding was performed for each wire in the examples and comparative examples using a commercially available wire bonder (IConn, manufactured by K&S). A Cu alloy lead frame plated with Ag was used as the lead frame, and a chip using Si was used as the semiconductor element. The above-mentioned lead frame plated with Ag was used as the electrode. Ball bonding was performed for the semiconductor element, and wedge bonding was performed for the lead frame. The ball formation was performed under a flow of N2 + 5% H2 gas at 0.4 L / min or more and less than 0.6 L / min.

[0086] <Scrub Evaluation> In the scrub evaluation, the number of scrubs during wedge bonding, which is usually required at least two times, was reduced to one or zero (no scrub) times (no scrub) to bond the wires. The bonding temperature was a low temperature of 150°C, the load conditions during bonding were 50 to 80 gf, and the USG Current setting value for ultrasonic vibration was adjusted in the range of 15 to 40. Regarding the scrub conditions, the scrub amplitude was set to a range of 2.5 to 3.5 μm, and the scrub frequency was adjusted in the range of 170 to 250 kHz. The scrub mode was selected as in-line, and the scrub movement direction was parallel to the wire direction. 200 wires were connected, and the number of non-adhesion that occurred during bonding due to peeling or connection failure such as wire bonder stop was counted. This was performed twice for each wire to calculate the average number of connection failures, and evaluation was performed according to the following criteria. The evaluation results are shown in the "bondability" column in Table 1.

[0087] Evaluation criteria: ◎:0 ○:1~3 △:4~6 ×:7 or more

[0088] <Loop shape stability> The loop shape stability (reproducibility of the loop profile) was tested and evaluated as follows for the formation of a long-span trapezoidal loop and for the formation of a short-span high-step loop.

[0089] (1) Stability of loop shape when forming a long-span trapezoidal loop 144 trapezoidal loops were connected to achieve wire lengths of 5 mm and loop heights of 0.4 mm, which are stricter than normal loop formation conditions. The loops were observed under an optical microscope, and any bends of 0.2 mm or more were judged to be defective, and evaluated according to the following criteria. The amount of bend was determined by connecting two joints with a straight line and measuring the distance from said line to the maximum bend. The evaluation results are shown in the "Long trapezoid" column in the "Loop shape stability" column of Table 1.

[0090] Evaluation criteria: ◎: No defects ○: 1 to 3 defects △: 4 to 7 defects ×: 8 or more defects

[0091] (2) Stability of loop shape when short-span high-step loop is formed 200 high-step loops were connected with a wire length of 0.6 mm and a height difference of 0.5 mm from the wedge junction to the ball junction. The loops were observed with an optical microscope, and if the amount of bending was 0.05 mm or more, it was judged to be defective, and evaluated according to the following criteria. The evaluation results are shown in the "Short length high step" column in the "Loop shape stability" column in Table 1.

[0092] Evaluation criteria: ◎: No defects ○: 1 to 3 defects △: 4 to 7 defects ×: 8 or more defects

[0093] [Capillary life] To conduct a bonding test that accelerates capillary contamination and clogging, a capillary with a small hole diameter of 25 μm was used to connect 50,000 trapezoidal loops with a wire length of 1.5 mm at a bonding temperature of 150°C and two scrubs. The capillaries were then removed from the wire bonder and observed under an optical microscope. The number of defects with dirt, deposits, shavings, etc. measuring 3 μm or more on the tip and inside of the capillary were counted and evaluated according to the following criteria. The evaluation results are shown in the "50,000 bonds" column in the "Capillary life" column of Table 1.

[0094] Evaluation criteria: ◎: Number of defects: 0 ○: Number of defects 1 △: Number of defects 2 ×: Number of defects is 3 or more

[0095] The case where 200,000 trapezoidal loops were connected under the same conditions as above was also evaluated, and the evaluation was performed according to the following criteria. The evaluation results are shown in the "200,000 bond" column in the "Capillary life" column of Table 1.

[0096] Evaluation criteria: ◎: Number of defects: 0 ○: Number of defects 1~2 △: Number of defects 3~4 ×: Number of defects is 5 or more

[0097] The evaluation results of the examples and comparative examples are shown in Table 1.

[0098] [Table 1]

[0099] It was confirmed that in all of Examples No. 1 to 16, the ratio Cu[II] / Cu[I] measured by XPS was within the range of the present invention, and good bondability was exhibited even when the number of scrubs during bonding was reduced to 1 or 0. The total of Cu[I] and Cu[II] measured by XPS was 50% or more in all of the Examples. In addition, it was confirmed that Examples 1 to 5, 7 to 11, 13, 15 and 16 had a ratio [Cu(OH)2] / [CuO] measured by XPS that was within a suitable range, and had excellent loop shape stability even when a long-span loop or a short-span high-step loop was formed. It was confirmed that in Examples 1, 2, and 4 to 16, the ratio [CuO] / [Cu2O] measured by XPS was in a suitable range, resulting in an excellent capillary life. On the other hand, in Comparative Examples No. 1 to 4, the ratio Cu[II] / Cu[I] measured by XPS was outside the range of the present invention, and when the number of scrubs during bonding was reduced to 1 or 0, poor connection occurred, and the loop shape stability and capillary life were also poor.

Claims

1. Cu, Cu measured by X-ray photoelectron spectroscopy (XPS) on the wire surface 2 O, CuO, Cu(OH) 2 The total of the percentages is 100%, and the Cu equivalent to Cu 1 valence is 2 The ratio of CuO, Cu(OH) corresponding to divalent Cu relative to the ratio of O (Cu[I]) 2 The copper bonding wire is characterized in that the ratio of Cu[II] / Cu[I], which is the total ratio (Cu[II]), is in the range of 0.8 to 12.

2. The ratio of CuO to Cu(OH) [CuO] measured by the X-ray photoelectron spectroscopy (XPS) 2 The ratio of Cu(OH) 2 ] is the ratio of [Cu(OH) 2 2. The copper bonding wire according to claim 1, wherein the ratio of [CuO] / [CuO] is in the range of 1 to 5.

5.

3. Cu as measured by the X-ray photoelectron spectroscopy (XPS) 2 The ratio of O [Cu 2 The ratio of CuO to CuO is [CuO] / [Cu 2 The copper bonding wire according to claim 1 or 2, characterized in that [O] is in the range of 0.3 to 6.

4. The copper bonding wire according to any one of claims 1 to 3, wherein the sum of Cu [I] and Cu [II] is 50% or more.

5. The copper bonding wire according to any one of claims 1 to 4, characterized in that it contains one or more selected from the group consisting of Pd, Pt, Ag, and Rh, and the total concentration thereof is in the range of 100 to 6000 ppm by mass.

6. The copper bonding wire according to any one of claims 1 to 5, having a diameter of 15 µm or more and 100 µm or less.

7. The copper bonding wire according to any one of claims 1 to 6, which is for use in a semiconductor device.

Citation Information

Patent Citations

  • Semiconductor device and manufacture thereof

    JP1985224237A

  • Copper alloy wire for connecting semiconductor element

    JP1986048543A

  • Method of manufacturing semiconductor device

    JP2018046242A

  • Corrosion and Moisture Resistant Copper Based Bonding Wire Containing Nickel

    JP2018503743A

  • Semiconductor device connection high purity copper fine wire

    WO2013099413A1